PENERAPAN MODEL PEMBELAJARAN QTL DAN RME DALAM PEMBELAJARAN MATEMATIKA - Ira Mirantika Sari (Universitas PGRI Adi Buana Surabaya, 2015)
This research is conducted by the fact that occurs until now , the results of learning about mathematics students still have low level, both on the level of education primary and the level of middle class .Considering the importance of mathematics in learning, there are kinds of classroom that are pleasing and mathematical connects with daily life can be used in learning math the way kind of classroom QTL and RME. The problem of the formulation of this research is no difference whether the results of learning mathematics material system of equations and inequality between students that were taught with a model of learning QTL and the model of learning RME in a class XSMKKartika 1 Surabaya ?.The purpose of this research is to know about differences between the results of learning mathematics material system of equations and inequality so students that were taught with a model of learning qtl and the model of learning rme in a class XSMKKartika 1 Surabaya . Including research experiment this kind of research.The population in this research is vocational school students SMK Kartika 1 Surabaya with the sample class X AK 1 is the class got learning RME and a class X AK 2 is a class of learning QTL received .The sample collection technique uses purposive sampling techniques.Data collection method uses the test and documentation .While a method of statistical data analysis using data analysis using t-test . Based on analisis from the results of data, obtained thitung = -2,098 and ttabel = 1,995.So we can conclude that that there is difference of the results between learning about mathematics matter system of equations and inequality, is students who are taught with a model of learning QTL and kind of classroom RME in class XSMKKartika 1 Surabaya . Keywords: QTL, RME, test student learning outcomes